Impact of dehydration on the physiochemical properties of Nostoc calcicola BOT1 and its untargeted metabolic profiling through UHPLC-HRMS - Yadav, Priya; Singh, Rahul Prasad; Alodaini, Hissah Abdulrahman; Hatamleh, Ashraf Atef; Santoyo, Gustavo; Kumar, Ajay; Gupta, Rajan Kumar (Frontiers in Plant Science, 2023)
The present study was conducted with an aquatic, diazotrophic cyanobacterial strain Nostoc calcicola BOT1 collected from Agricultural field of Banaras Hindu University, to evaluate the effects of different dehydration treatments such as air dried (AD), and desiccator dried (DD) at different time interval on the various physicochemical properties of N. calcicola BOT1. The impact of dehydration significantly affects the photosynthetic efficiency, pigments, various biomolecules like carbohydrate, lipids, proteins, osmoprotectants, stress biomarkers, and non-enzymatic antioxidants. In details the pigments like chlorophyll-a, and phycobiliproteins were decreased while carotenoid and scytonemin concentrations increased significantly. Further, protein content was decreased, and carbohydrate content was increased as the dehydration progressed. Additionally, the dehydration enhanced the stress biomarkers like trehalose, proline, malondialdehyde (MDA), H2O2, total flavonoids, and phenol content in the dehydrated cells. Our study revealed that the water stress damaged the filaments during dehydration due to alteration of physicochemical properties. Further UHPLC-HRMS analysis was used tocarried out to determine the metabolic profiling of 96 h DD and control mats. During analysis,Ddipeptides, amino acids, fatty acids, lipids, polyphenols, and phenolic acids were detected. AHowever several fold decreases in the level of amino acids occurs while the content of phenolic content, fatty acids, and lipids increase. The Cchanges in the metabolic activity during dehydration conditions highlighted pools of metabolites that affect the physiological and biochemical adjustments inof N. calcicola BOT1 that slightly reduced dehydration impacts. These results indicate. Our study showed that the increased concentration of biochemical and non-enzymatic antioxidants in the dehydrated mats, can be used to stabilize the unfavorable environmental conditions. In addition the strain and N. calcicola BOT1 can be used as a biofertilizer in the semi-arid regions.